2012
DOI: 10.1074/jbc.m111.324194
|View full text |Cite
|
Sign up to set email alerts
|

Siglec-15 Protein Regulates Formation of Functional Osteoclasts in Concert with DNAX-activating Protein of 12 kDa (DAP12)

Abstract: Background: ITAM-harboring DAP12 contributes to functional osteoclast formation. Results: Siglec-15 is NFAT2-inducible and functions with DAP12 to promote functional osteoclast development. Conclusion: Siglec-15 links RANKL-RANK-NFAT2 signaling with ITAM-mediated signaling during osteoclast development. Significance: Our results provide new insights into how DAP12 transduces extracellular signals into osteoclasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 39 publications
(54 reference statements)
5
73
0
Order By: Relevance
“…A recent study reported the overexpression of Siglec-15 in giant cell tumors of the bone, which are characterized by abundant osteoclast-like cells, and in agreement with our results, the authors observed dramatic up-regulation of Siglec-15 mRNA in differentiating HOPs and RAW264.7 cells (5). The effect of Siglec-15 RNAi on osteoclast differentiation has since been independently confirmed in mouse bone marrow macrophages (6). Importantly, we also found that, besides osteoclasts, Siglec-15 mRNA expression is nearly absent from a panel of normal human tissues (3).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…A recent study reported the overexpression of Siglec-15 in giant cell tumors of the bone, which are characterized by abundant osteoclast-like cells, and in agreement with our results, the authors observed dramatic up-regulation of Siglec-15 mRNA in differentiating HOPs and RAW264.7 cells (5). The effect of Siglec-15 RNAi on osteoclast differentiation has since been independently confirmed in mouse bone marrow macrophages (6). Importantly, we also found that, besides osteoclasts, Siglec-15 mRNA expression is nearly absent from a panel of normal human tissues (3).…”
supporting
confidence: 92%
“…Following completion of the current study, Ishida-Kitagawa et al (6) published a detailed analysis of the structural elements of Siglec-15 required for osteoclastogenesis. The authors knocked down Siglec-15 expression in mouse bone marrowderived macrophages, impairing their ability to differentiate into osteoclasts, and attempted to rescue this defect with various Siglec-15 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…While not considered part of the immune system, they are derived from a monocyte precursor through RANKL stimulation 130 . Recently, Siglec-15, which is highly conserved in vertebrates 131 , was shown to be constitutively expressed in osteoclasts 132, 133 . Mice lacking Siglec-15 develop mild osteopetrosis, a condition that is characterized by dense bone 134, 135 .…”
mentioning
confidence: 99%
“…13) In addition, sugar-binding proteins such as siglec, which interact with sialic acid, and galectins, which interact with Galβ1-4GlcNAc, also have important roles in osteoclastogenesis. [14][15][16][17][18][19] Therefore, in order to clarify the potential for GlcN-mediated glycosylation modification, we investigated the effect of GlcN treatment on the pattern of glycosylation using lectin blotting of cell extracts with SSA, MAM, RCA120, PHA-E 4 , Con A, and LCA, which mainly recognize α2,6-linked sialic acid, α2,3-linked sialic acid, Galβ1-4GlcNAc, bisecting GlcNAc, high mannose type Nglycan, and N-glycan core modified with fucose, respectively (Figs. 2B-G).…”
Section: Glcn Suppresses the Osteoclastic Differentiation Of Raw264 Cmentioning
confidence: 99%